1992
DOI: 10.1136/ard.51.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Differences in HLA antigens between patients with mixed connective tissue disease and systemic lupus erythematosus.

Abstract: Patients with mixed connective tissue disease (MCTD, n=32)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 25 publications
0
8
1
Order By: Relevance
“…Serologically defined DR4 was reported to be associated with anti-U1 RNP antibody in Caucasians from various origins (12)(13)(14)(15)(16), but we did not detect a DR4 association in Japanese, as described in a previous serologic analysis (17). If an ANA and HLA association is postulated to exist worldwide among many ethnic groups, this discrepancy could be explained by a different distribution of HLA class I1 alleles.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Serologically defined DR4 was reported to be associated with anti-U1 RNP antibody in Caucasians from various origins (12)(13)(14)(15)(16), but we did not detect a DR4 association in Japanese, as described in a previous serologic analysis (17). If an ANA and HLA association is postulated to exist worldwide among many ethnic groups, this discrepancy could be explained by a different distribution of HLA class I1 alleles.…”
Section: Discussioncontrasting
confidence: 46%
“…These observations indicate that patients with anti-U1 RNP antibody are heterogeneous, both clinically and serologically. Several studies of immunogenetic correlations with anti-U 1 RNP antibody employing serologic HLA typing have shown an increased frequency of DR4 in white patients (12)(13)(14)(15)(16) and of DQ3 in Japanese patients (17), but some investigators failed to detect any associations (1 8,19). Recent molecular immunogenetic analysis has revealed an increased frequency of one of the DQ3 subantigens, DQ8 (DQB1*0302), in white patients with S L E and anti-U1 RNP antibody, as compared with race-matched healthy controls (20).…”
Section: Discussionmentioning
confidence: 99%
“…A cornerstone in the advocacy of the existence of "MCTD" is the association between antibody production and HLA haplotypes. Different studies have demonstrated an association between the presence of anti-U1RNP antibody and an HLA-DR4-specific haplotype [20][21][22]34]. Genth et al [23] studied 35 patients with anti-U1RNPpositive ARD, with a mean disease duration of 6.3 years.…”
Section: Immunologic and Genetic Featuresmentioning
confidence: 99%
“…This is due to an apparently similar clinical picture in some anti-RNP-positive patients with overlapping features of ARD, a tendency to the insidious development of PAH (pulmonary arterial hypertension) and ILD (interstitial lung disease), and relatively uncommon renal or neurological involvement. A genetic association between HLA haplotype and anti-U1RNP antibodies was discovered, which some have interpreted as supporting the concept of MCTD [20][21][22]. However, other studies demonstrated that this linkage did not correlate with clinical disease expression, merely with antibody production [23,24].…”
Section: Introduction: a Historical Perspectivementioning
confidence: 99%
“…On the other hand, several recent reports showed that MCTDwas a distinct disease entity (3)(4)(5). Regarding a genetic markers, MCTD-associated HLAis distinct from the SLE-and SSc-associated HLAin Japanese and Caucasian patients (3,6,7). Furthermore, as a clinical feature of this disease, pulmonary hypertension (PH) is a characteristic organ involvement and is the most frequent cause of death, especially in Japan (8)(9)(10).…”
mentioning
confidence: 99%